IMPACTS CAUSED BY THE DOLLAR ON THE DAIRY CATTLE FARMING AT ESTÂNCIA VITÓRIA SUD MENNUCCI - SP: a case study - Silva Lucatto, João Vitor; Silva Batista, Maurício da; Santos de Lima, Edy Carlos; Manoel Porto, Alessandra; Lopes Santos de Lima, Greice Kelli; Araujo Ortin, Sileno Marcos (Revista Interface Tecnológica, 2022)
This article presents the analysis of the variation in the prices of used inputs in dairy cattle, through a case study, which was applied at Estância Vitória, located in Sud Mennucci - SP. The study was carried out from March 2020 to April 2021, a period in which an analysis of the prices of all used inputs directly in animal feed, in which the following factors of price variation were verified: the scarcity of rain, the emergence of coronavirus (Covid19), high dollar value due to the economic crisis that Brazil is going through and the lack of raw material that is related to the water crisis. The results indicate that the price of a liter of milk did not follow the variation in which the dollar suffered in the period; only that the used inputs to feed the animals changed compared to the dollar, but the variation of the inputs was even greater.
Keywords: Dairy cattle farming; Variation; Inputs; Dollar; Milk